Method for Angiographically Guided Fine-Needle Diathermy in the Treatment of Corneal Neovascularization. Issue 7 (July 2016) - Romano, Vito; Steger, Bernhard; Brunner, Matthias; Ahmad, Sajjad; Willoughby, Colin E.; Kaye, Stephen B.
Abstract : Purpose: To describe a method to assess corneal neovascular (CoNV) complexes and identify feeder vessels for selective arterial fine-needle diathermy (FND). Methods: In patients with CoNV, color photography and corneal indocyanine green angiography (ICGA) and fluorescein angiography are performed. After injection of indocyanine green and sodium fluorescein dye, videography and single-frame images of the region of interest are recorded. Videography is used to measure the time to leakage to assess vessel maturity to guide medical treatment and to discern afferent from efferent vessels. Single-frame images are then selected to locate the number of afferent vessels for surgery, which are selectively cut with a 25-gauge marked needle for the application of FND. Results: Angiography using fluorescein and indocyanine green allows the characterization of CoNV based on assessment of both morphologic (ICGA) and functional (fluorescein angiography) parameters. The time to leakage of fluorescein dye provides important functional information on vessel maturity and helps discern whether medical treatment should be followed before surgical. ICGA allows the identification and delineation of afferent feeder vessels even in the presence of corneal opacities affecting biomicroscopic visibility. Colocalizing the afferent vessel to a visible venous landmark or branch is helpful for placement of the incision and application of FND. Using the described approach, angiographically identified feeder vessels can be selectively treated by FND with minimal thermal energy applied to the corneoscleral limbus. Conclusions: The described method for angiographically guided assessment of CoNV is a useful approach for guiding the medical and surgical treatment of CoNV. Abstract : Supplemental Digital Content is Available in the Text.